Fique Fiber Tensile Elastic Modulus Dependence with Diameter Using the Weibull Statistical Analysis (2015)
Fique is a plant native of Colombia with fibers extracted from its leaves presenting relevant physical characteristics and mechanical properties for possible engineering applications, such as reinforcement of polymer composites. The main physico-mechanical properties of the fique fiber have already been investigated for both untreated and mechanically treated fibers. The statistical distribution of the fique fiber diameter was analyzed and the effect of microfibrillar angle on the tensile strength and elongation was determined. However, the correlation of mechanical properties with the fiber diameter is yet to be determined. Thus, the present work evaluated the tensile elastic modulus dependence of the fique fiber as a function of its diameter. By means of the Weibull statistical analysis, it was found that an inverse correlation adjusted the elastic modulus with the equivalent diameter through a hyperbolic type of mathematical relationship. Similar correlation have been found for several lignocellulosic fibers not only by the research group of the present work but also other international groups The results are compared and discussed.